2020
DOI: 10.3390/insects11070415
|View full text |Cite
|
Sign up to set email alerts
|

RNAi in Insects: A Revolution in Fundamental Research and Pest Control Applications

Abstract: In this editorial for the Special Issue on ‘RNAi in insect pest control’, three important applications of RNA interference (RNAi) in insects are briefly discussed and linked to the different studies published in this Special Issue. The discovery of the RNAi mechanism revolutionized entomological research, as it presented researchers with a tool to knock down genes, which is easily applicable in a wide range of insect species. Furthermore, RNAi also provides crop protection with a novel and promising pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…After the Nobel prized discovery of RNA interference (RNAi) as a basic mechanism of post-transcriptional gene silencing by double-stranded RNA (dsRNA) [126] RNAi has become a powerful experimental tool for determining gene functions, had an immense impact on biomedical research and found its application in the management of insect pests. Evolutionarily conserved in all eukaryotes, the mechanism of RNAi is involved in different processes including internal gene regulation (micro RNA or miRNA pathway), genome protection against transposons (piwi-interacting RNA or piRNA pathway) and defence against viral infections (small interfering RNA or siRNA pathway) [127]. Althought the siRNA pathway in insects mostly represents the first line of defense against viral RNA, it can be exploited for introduction of specific dsRNA that, through mechanism of RNAi, can initiate degradation of complementary endogenous insect mRNA.…”
Section: Silencing Vital Genesmentioning
confidence: 99%
“…After the Nobel prized discovery of RNA interference (RNAi) as a basic mechanism of post-transcriptional gene silencing by double-stranded RNA (dsRNA) [126] RNAi has become a powerful experimental tool for determining gene functions, had an immense impact on biomedical research and found its application in the management of insect pests. Evolutionarily conserved in all eukaryotes, the mechanism of RNAi is involved in different processes including internal gene regulation (micro RNA or miRNA pathway), genome protection against transposons (piwi-interacting RNA or piRNA pathway) and defence against viral infections (small interfering RNA or siRNA pathway) [127]. Althought the siRNA pathway in insects mostly represents the first line of defense against viral RNA, it can be exploited for introduction of specific dsRNA that, through mechanism of RNAi, can initiate degradation of complementary endogenous insect mRNA.…”
Section: Silencing Vital Genesmentioning
confidence: 99%
“…We investigated the possibility of using MIF genes as targets for RNAi-based insect control in plants. Several studies have shown that aphids are sensitive to double-stranded (ds) RNA (Jaubert-Possamai et al 2007;Pitino et al 2011) and therefore are amenable to RNAi strategies in crop protection (Christiaens et al 2020;Liu et al 2020). In 2015, we showed that dsRNA derived from the gene encoding salivary sheath protein (SHP), when expressed in barley, strongly reduced the survival of the grain aphid Sitobion avenae (Sa) (Abdellatef et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi), mediated by double-stranded RNA (dsRNA), has been shown to be an effective means of controlling a large number of agricultural pests ( Upadhyay et al, 2011 ; Zhang et al, 2015 ; Niu et al, 2018 ; Liu et al, 2019 ; Christiaens et al, 2020 ). Recent reports have also identified a range of genes that could be used as RNA targets to control aphids.…”
Section: Introductionmentioning
confidence: 99%